2004
DOI: 10.1152/ajpcell.00007.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A increases permeability through tight junctions by removal of specific claudin isoforms

Abstract: . Ochratoxin A increases permeability through tight junctions by removal of specific claudin isoforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(78 citation statements)
references
References 27 publications
9
67
1
1
Order By: Relevance
“…Cldn3 function in the vertebrate intestine has yet to be clearly defined. Recent studies have reported that treatment of Caco-2 epithelia with a mycotoxin (ochratoxin A), caused a marked decrease (ϳ87%) in Cldn3 expression, which was coupled to a substantial reduction in TER and concomitant increase in paracellular permeability (29). These observations are in general accord with studies relating pathological dysfunction in the gastrointestinal tract to increased intestinal permeability, a phenomenon normally associated with reduced TJ protein expression and changes in TJ protein distribution (7).…”
Section: Discussionsupporting
confidence: 62%
“…Cldn3 function in the vertebrate intestine has yet to be clearly defined. Recent studies have reported that treatment of Caco-2 epithelia with a mycotoxin (ochratoxin A), caused a marked decrease (ϳ87%) in Cldn3 expression, which was coupled to a substantial reduction in TER and concomitant increase in paracellular permeability (29). These observations are in general accord with studies relating pathological dysfunction in the gastrointestinal tract to increased intestinal permeability, a phenomenon normally associated with reduced TJ protein expression and changes in TJ protein distribution (7).…”
Section: Discussionsupporting
confidence: 62%
“…Protein was extracted from NHEK cells according to the method described by McLaughlin et al (19) ]) containing aprotinin (10 g/ml), leupeptin (10 g/ml), and pepstatin A (10 g/ml) and then incubated on ice for 30 min. Following centrifugation in a microcentrifuge, the supernatant was recovered in a clean Eppendorf tube and used for analysis of TJ protein expression.…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were subsequently washed and incubated with horseradish peroxidase-conjugated secondary antibodies. The immunoblots were developed using enhanced chemiluminescence (Amersham, Bucks, United Kingdom), and densitometry was performed as described by McLaughlin et al (19).…”
Section: Methodsmentioning
confidence: 99%
“…Sallee and Burridge (2009) reported that occludin and ZO-1 were dephosphorylated by DEP-1 in MCF10A human mammary epithelial cells treated with ochratoxin A. An increase of permeability was caused by the removal of claudin-3 and 4 by ochratoxin A treatment in Caco-2 cells (McLaughlin et al 2004). As such, we tested the effect of patulin and depletion of DEP-1 on the phosphorylation status of claudin-4.…”
Section: Effects Of Patulin or Knockdown Of Dep-1 On The Epithelial Bmentioning
confidence: 99%